Analisis Penerapan Central Bank Digital Currency Dalam Ekonomi Syariah: Perspektif Hukum Dan Keuangan Islam - Zuchroh, Imama (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2025)
The development of digital financial technology has encouraged various central banks in the world to develop Central Bank Digital Currency (CBDC). This study examines the implementation of CBDC from the perspective of sharia economics with a focus on Islamic legal and financial aspects. An analysis was carried out on the conformity of CBDC characteristics with sharia principles, such as the prohibition of riba, gharar, and maysir, as well as their potential impact on the Islamic financial system. The methodology used is literature research with a qualitative descriptive approach, analyzing various literature and documents related to CBDC and sharia economic law. The results of the study show that the implementation of CBDC can be in line with sharia principles if it is designed by paying attention to several critical aspects: the use of transparent technology, a usury-free transaction mechanism, and governance that is in accordance with sharia maqashid. The study also identifies the potential of CBDCs in improving the efficiency of the Islamic financial system, expanding financial inclusion, and strengthening the supervision of financial transactions.